2015
DOI: 10.1038/cmi.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of squamous cancer growth in a mouse model by Staphylococcal enterotoxin B-triggered Th9 cell expansion

Abstract: Currently, therapy for squamous cancer (SqC) is unsatisfactory. Staphylococcal enterotoxin B (SEB) has strong immune regulatory activity. This study tests the hypothesis that SEB enforces the effect of immunotherapy on SqC growth in a mouse model. C3H/HeN mice and the SqC cell line squamous cell carcinoma VII were used to create an SqC mouse model. Immune cell assessment was performed by flow cytometry. Real-time RT-PCR and western blotting were used to evaluate target molecule expression. An apoptosis assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…We previously reported that TGF-β-expanded Vδ2 T cells also produce high amounts of IL-9, 17 but this is most likely not the reason for the enhanced cytotoxicity observed in our present study, since neutralizing anti-IL-9 antibodies did not affect the cytotoxic activity. Miao et al described a direct cytotoxic effect of IL-9 (produced by Th9 T cells) on squamous cancer cells 27 and Nalleweg et al reported that IL-9 counteracted the proliferation of an epithelial tumor cell line. 28 However, most other studies reporting a beneficial effect of IL-9-producing T cells on antitumor immunity were in vivo studies, in which IL-9 indirectly affected anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that TGF-β-expanded Vδ2 T cells also produce high amounts of IL-9, 17 but this is most likely not the reason for the enhanced cytotoxicity observed in our present study, since neutralizing anti-IL-9 antibodies did not affect the cytotoxic activity. Miao et al described a direct cytotoxic effect of IL-9 (produced by Th9 T cells) on squamous cancer cells 27 and Nalleweg et al reported that IL-9 counteracted the proliferation of an epithelial tumor cell line. 28 However, most other studies reporting a beneficial effect of IL-9-producing T cells on antitumor immunity were in vivo studies, in which IL-9 indirectly affected anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…For the surface labeling of adherent tumor cells, the cells were detached by accutase. For intracellular staining the following mAb were used: anti-granzyme A (clone: CB9), anti-granzyme B (clone: GB11), anti-IFN-γ (clone: 4S.B3), anti-IL-9 (clone: MH9A3), anti-TNF-α (clone: 359-81-11), anti-perforin (clone: dG9), IgG1 (clone: MOPC-21) and IgG2b (clone: [27][28][29][30][31][32][33][34][35] isotype controls (all from BD Biosciences). For intracellular staining, cells were stimulated for 6 h with 10 ng/mL 12-O-tetradecanoylphorbol-13-acetate (TPA; Sigma Aldrich, Missouri, USA) and 1 µg/mL ionomycin (EMD Millipore/Calbiochem, Darmstadt, Germany) as indicated; 3 µM monensin (EMD Millipore/ Calbiochem) was added 4 h before fixation in each case.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Th9 cells themselves can exert enhanced antitumor activity (41), but IL-9 might also act indirectly via mast cells (8) or recruitment of dendritic cells to the tumor site (7). Significant numbers of γδ T cells are present among tumor-infiltrating lymphocytes (TILs) in many cancer types (42), and, in fact, the proportion of γδ T cells among TILs is the best predictive parameter across 25 human tumor entities (43).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that Id3 can regulate the antitumor immunity of experimental melanoma-bearing mice by negatively regulating the differentiation of Th9 cells [86]. A metabolite of a bacterium, staphylococcal enterotoxin B (SEB) can induce the proliferation of Th9 cells and inhibit the growth of mouse squamous carcinoma [87]. It has also been reported that SEB can promote the induction of specific Th9 cells to inhibit glioma cell growth [88] ( Table 3).…”
Section: Different Factors Regulate the Antitumor Effect Of Th9 Cellsmentioning
confidence: 99%